SISTEM PEWARISAN APABILA PEWARIS DAN AHLI WARISNYA MENINGGAL DUNIA PADA SAAT BERSAMAAN DITINJAU BERDASARKAN KITAB UNDANG -UNDANG HUKUM - Ayu Ananda Dwi Satyawati, Ni Made; Putrawan, Suatra (Kertha Semaya : Journal Ilmu Hukum; Vol. 02, No. 06, Oktober 2014)
This paper titled Systems of Inheritance if the Inheritor and the Heir dies at thesame time are reviewed by the Burgerlijk Wetboek, which is also the subject matter tobe discussed in this paper. The background of this paper is the problem posed in theinheritance if the heir and his heir died in a disaster for which between them can’t bedetermined who died first. The purpose of this paper is to understand the system ofinheritance if the heir and the heir dies at the same time based on the Book of the Lawof Civil Law. This paper uses the normative method by analyzing the problems with thelaw and relevant literature. The conclusion of this paper is that the inheritance systemin which the heir and his heir died at the same time because of a calamity and betweenthem can’t be known in advance who the deceased was not able to transfer theinheritance. Article 831 and Article 894 of the Burgerlijk Wetboek is the basis of theoccurrence of an inheritance can’t be due to the heir and his heir died at the same time.
Keywords: System of Inheritance, Inheritor, Heir, Burgerlijk Wetboek